A Europe wide acceptable mismatch program will enable transplantation of long waiting highly sensitised patients with a compatible donor - Mumford, Lisa; Fuggle, Susan V; Martorell, Jaume; Slavcev, Antonij; Iniotaki, Aliki; Haasnoot, Geert W; Heidt, Sebastiaan; Claas, Frans H J (Transplant immunology, 2021)
Immunisation against Human Leucocyte Antigens (HLA) can be caused by pregnancy, blood transfusion, or organ transplants. The HLA antibody status of a given patient significantly influences their access and waiting time to transplant. For some highly sensitised patients (HSP) there is hardly any suitable donor available in the deceased donor pool of their allocation organisation and therefore they wait a very long time before being offered a kidney for transplant. Especially patients with rare HLA phenotypes in relation to the actual donor pool are waiting extremely long. As HLA phenotypes are different in the various European populations, we hypothesized that extension of the donor pool outside the respective allocation system will increase the chance of receiving a compatible transplant for this subgroup of highly sensitised patients. One of the objectives of the EUROSTAM project, (a Europe-wide Strategy to enhance Transplantation of highly sensitised patients on the basis of Acceptable HLA Mismatches) was to develop a tool to compare the chance of transplanting HSP in different European populations with donor organs from within and outside their own donor pool. Information on the HLA type and ABO blood group of the actual donor population, as well as the acceptable mismatches of long waiting HSP were obtained from the EUROSTAM partner organizations i.e. Eurotransplant (ET), UK National Health Service Blood and Transplant (NHSBT), Barcelona, Prague and Athens. Results from simulations using the newly developed tool shows that 195 (27%) of the 724 long waiting highly sensitised patients registered at each partner organisation have increased chances of transplant in a different European donor pool. This makes a strong case for sharing kidneys between European countries for selected difficult to transplant patients.
Keywords: imunizace; příjemce transplantátu; Transplantation; testování histokompatibility; HLA; Waiting Lists; Histocompatibility Testing; seznamy čekatelů; Europe; Highly sensitised patient; Histocompatibility; Kidney; Tissue Donors; Transplant Recipients; HLA antigeny; dárci tkání; Evropa; Acceptable mismatch; lidé; Kidney Transplantation; transplantace ledvin; Humans; HLA Antigens; histokompatibilita; Immunization